Synthesis and Characterization of Novel Diorganotin(IV) Complexes Derived from N-Methyl-phenethyl Dithiocarbamate and Bis(2-ethoxyethyl) Dithiocarbamate - Pim, Norraphat Uttraphan; Awang, Normah; Mohamad, Rapidah; Abdul Aziz, Yang Farina; Kamaludin, Nurul Farahana (Asian Journal of Chemistry, 2018)
Organotin(IV) dithiocarbamate complexes are extensively studied worldwide as they have proven to exhibit promising anticancer, antimicrobial and larvicidal properties. In this study, three new organotin(IV) dithiocarbamate complexes have been successfully synthesized via in situ reaction between the appropriate secondary amines with carbon disulphide and organotin(IV) salts, in a basic solution at temperature below 4 °C. The complexes were characterized by CHNS elemental analysis, FTIR and 1H, 13C and 119Sn NMR. All complexes displayed the important NCS2 peak from 200.02-201.35 ppm in 13C NMR, signifying the presence of the dithiocarbamate ligand. The complexes also produced the essential IR bands, ν(C-N), ν(C-S) and ν(Sn-C) in the ranges 1489 to 1479 cm–1, 986.2 to 971.2 cm–1 and 568.2 to 550.8 cm–1, respectively. From the 119Sn NMR, both the ligands were suggested to coordinate to the tin atom in a bidentate manner in all three complexes.